PENGARUH SISTEM PENGENDALIAN INTERN, SISTEM INFORMASI AKUNTANSI, DAN KOMPETENSI PEJABAT PENATAUSAHAAN KEUANGAN TERHADAP NILAI INFORMASI PELAPORAN KEUANGAN DAERAH (Studi Pada Satuan Kerja Perangkat Daerah Kabupaten Rokan Hilir) - Putri, Adria Pratama; Taufik, Taufeni; ', Susilatri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This study aim was finding out the effect of the internal control system, the accounting information system and the financial administration officials competence on the value of local financial reporting information at Regional Working Unit Rokan Hilir regency. The respondents were head of finance sectionand expenditure treasurer. The sample was determined by purposive sampling technique. Total of respondents in this research are 66 of respondents. The data of this research used was primary data. The method of data collection was questionnaire. The technique of data analysis was multiregression analysis using SPSS version 20.00. The result showed that the internal control system, accounting information system, and the financial administration officialcompetence an effect on the value of local financial reporting information. The coefficient of determination showed the internal control system, accounting information system, and the financial administration official competence an effecton the value of local financial reporting information amounted to 51,8% and the remaining 48,2% an effected by other variables that’s not included in this study as the information technology, etc.Keywords: Information value, internal control, accounting information, and competence administration official